EDUCAÇÃO PERMANENTE: ESTRATÉGIA PARA REPENSAR O PROCESSO DE TRABALHO E A ASSISTÊNCIA DE PROFISSIONAIS DA SAÚDE - Menezes, Luana P.; Pinno, Camila; Guzzo, Patrícia C.; Corrêa, Camila F.; Resta, Darielli G.; Colomé, Isabel C. d. S.; Cocco, Marta; Jahn, Do C.; Silva, Luiz A. A. d.; Machado, Débora P. (Salão do Conhecimento, 2013)
Resumo